"Green" motor taxation: Issues and policy options in sub-Saharan Africa - Hazel Granger; Vedanth Nair; Harshil Parekh; David Phillips; Daniel Prinz; Edris Hussein Seid; Ross Warwick (Institute for Fiscal Studies (IFS), 2021)
Over the last 20 years, sub-Saharan African (SSA) countries have experienced significant economic growth and consequently growing levels of motorisation. Though overall levels of motorisation in SSA are still relatively low, with a high number of poor-quality vehicles concentrated in large cities, social and environmental problems associated with motoring are becoming more pressing. Because individual drivers do not consider the wider social impacts of their motoring, governments need to intervene to achieve efficient motoring outcomes. Government policies to address the problems arising from motoring can include non-tax policies, including regulation and enforcement. For example, roadworthiness tests on imported cars are a good policy option to improve vehicle quality (UNEP, 2020), whilst taking steps to improve road safety and licensing are important to reduce road fatalities (WHO, 2018). However, in this report, we focus on the use of tax policy to appropriately price the externalities of motoring. This report contributes to ongoing policy debates on motoring taxation in SSA by describing the principles of motoring taxation and key issues and policy options for the region. Where appropriate, we draw on case studies, including from the TaxDev programme's four partner countries (Ethiopia, Ghana, Rwanda and Uganda). Case studies are useful to understand particular design issues and challenges in more detail.
Keywords: 330; Kraftfahrzeug; Mineralölsteuer; Kraftfahrzeugsteuer; Steuerpolitik; Externer Effekt; Nachhaltigkeit; Subsahara-Afrika